The dynamics of signal triggering in a gp130-receptor complex. - Matadeen, R; Hon, W; Heath, J; Jones, E; Fuller, S (2007)
gp130 is a shared signal-transducing membrane-associated receptor for several hematopoietic cytokines. The 30 A resolution cryo-electron microscopy (cryo-EM) structure of the Interleukin 11(IL-11)-IL-11 Receptor-gp130 extracellular complex reveals the architecture and dynamics of this gp130-containing signaling complex. Normal-mode analysis reveals a repertoire of conformational changes that could function in signal triggering. This suggests a concerted mechanism of signaling involving all the components of the complex. This could provide a general mechanism of signal transfer for cytokines utilizing the JAK-STAT signaling cascade.